Marketing and customer loyalty : the extra step approach - Cavallone, Mauro (Springer, 2017)
This book analyzes the evolution of marketing and the ways in which marketing actions can be rendered more effective, before setting out a new approach to marketing, termed The Extra Step (TES) in recognition of the importance that it attributes to the final extra step in enhancing the effectiveness of marketing efforts. Readers will find clear description of the pathway from purchase to loyalty and the various means of developing customer loyalty. It is explained how the TES approach goes one step further by considering the consumer as a partner whose involvement during the production and fine tuning phase of products and services can help to increase the efficiency of customer loyalty actions implemented by companies. The theoretical analysis is supported by observations and empirical evidence relating to the concepts and benefits of the TES approach. These examples concern firms in Italy, Europe, and the United States, including insurance agencies, pharmaceutical companies and pharmacies, and food distribution companies. The TES approach is of wide relevance and especially valid for the service sector.
Keywords: Marketing.; Customer loyalty.; elektronické knihy; electronic books